2014
DOI: 10.1162/jocn_a_00506
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Read an Alphabet of Human Faces Produces Left-lateralized Training Effects in the Fusiform Gyrus

Abstract: Numerous functional neuroimaging studies have shown that most orthographic stimuli, such as printed English words, produce a left-lateralized response within the fusiform gyrus (FG) at a characteristic location termed the visual word form area (VWFA). We developed an experimental alphabet (FaceFont) comprising 35 face–phoneme pairs to disentangle phonological and perceptual influences on the lateralization of orthographic processing within the FG. Using functional imaging, we found that a region in the vicinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 58 publications
9
42
0
Order By: Relevance
“…These results converge with the neuroimaging findings of Moore et al (2014), who trained young adults to read the FaceFont orthography. After a two-week training period, participants were able to read simple texts written in FaceFont with high levels of comprehension at rates similar to beginning readers of written English.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…These results converge with the neuroimaging findings of Moore et al (2014), who trained young adults to read the FaceFont orthography. After a two-week training period, participants were able to read simple texts written in FaceFont with high levels of comprehension at rates similar to beginning readers of written English.…”
Section: Discussionsupporting
confidence: 87%
“…In her initial effort, AA1 attempted to learn all 35 of the phonograms in the FaceFont alphabet. AA1 correctly recalled only 5.71% of the face-phoneme mappings when tested after 11 prior exposures to the phonogram set, a level of performance well below that observed in healthy young adults (Moore et al, 2014). In AA1's second FaceFont learning opportunity, we investigated whether she could learn FaceFont phonograms more easily if they were presented in small subsets.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…Studies in humans have occasionally found shifts in selectivity as a function of training: Moore et al 37 found that learning to read an alphabet of human faces induces responsiveness to those faces in the left fusiform area. Moreover, the part of the brain that is selectively responsive to text in literate humans is, in illiterate people, responsive to faces 38 .…”
Section: Discussionmentioning
confidence: 99%